2018
DOI: 10.1002/mbo3.734
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of gut microbiota in wild and captive Malaysian Mahseer (Tor tambroides)

Abstract: Aims The aim of this study was to identify and compare the gut microbial community of wild and captive Tor tambroides through 16S rDNA metagenetic sequencing followed by functions prediction. Methods and results The library of 16S rDNA V3‐V4 hypervariable regions of gut microbiota was amplified and sequenced using Illumina MiSeq. The sequencing data were analyzed using Quantitative Insights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 80 publications
3
27
1
1
Order By: Relevance
“…In line with previous studies on T. tambroides and other fish species, our results indicated that gut microbiota of this species was dominated by the phylum Bacteroidetes, Proteobacteria, Tenericutes and Actinobacteria (Carda‐Diéguez et al, ; Hovda et al, ; Mohd Nosi et al., ; Tan et al, ). These phyla usually constitute the “core gut microbiota” of T. tambroides regardless of the diet type and represent up to 90% of fish intestinal microbiota (Mohd Nosi et al, ; Tan et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In line with previous studies on T. tambroides and other fish species, our results indicated that gut microbiota of this species was dominated by the phylum Bacteroidetes, Proteobacteria, Tenericutes and Actinobacteria (Carda‐Diéguez et al, ; Hovda et al, ; Mohd Nosi et al., ; Tan et al, ). These phyla usually constitute the “core gut microbiota” of T. tambroides regardless of the diet type and represent up to 90% of fish intestinal microbiota (Mohd Nosi et al, ; Tan et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous studies on T. tambroides and other fish species, our results indicated that gut microbiota of this species was dominated by the phylum Bacteroidetes, Proteobacteria, Tenericutes and Actinobacteria (Carda‐Diéguez et al, ; Hovda et al, ; Mohd Nosi et al., ; Tan et al, ). These phyla usually constitute the “core gut microbiota” of T. tambroides regardless of the diet type and represent up to 90% of fish intestinal microbiota (Mohd Nosi et al, ; Tan et al, ). The presence of similar bacterial phylum in the gut microbiota of different sodium alginate‐supplemented diets of T. tambroides as well as in multiple fish species indicates that these bacteria are involved in important host gut functions, such as digestion, nutrient absorption and immune response (Ghanbari, Kneifel, & Domig, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This genus is also found in freshwater aquatic environments and is rarely reported as pathogens in these animals, being a potential antagonist of pathogenic microorganisms from bacterial and fungal origin [64]. Less abundant and exclusive bacteria from the CON group such as bacteria from the genus Turicibacter and family Caldilineaceae have been reported in fish microbiota in natural environments [65,66]. Another bacteria little present, but with greater abundance in the SUP group, Ralstonia has been found in greater abundance in sea bass fed on functional diets, and its dominance possibly justified by the presence of essential oils in the diet [67].…”
Section: Discussionmentioning
confidence: 99%
“…High relative abundances of Cetobacterium and Aeromonas suggest that they are the core microbiota in IMCs. Anaerobic bacteria are most common in the fish gut and play a crucial role in digestion via decomposition of organic debris, phytoplankton and zooplankton (Borsodi et al ; Tan et al ). Though some methods are available now, because of its obligate anaerobic properties, culturing of Cetobacterium in atmospheric conditions is difficult and, therefore, their effects have never been tested in fish.…”
Section: Resultsmentioning
confidence: 99%